Different sea urchin RAG-like genes were domesticated to carry out different functions - Yakovenko, Iryna; Tobi, Dror; Ner-Gaon, Hadas; Oren, Matan (Frontiers in Immunology, 2023)
The closely linked recombination activating genes (RAG1 and RAG2) in vertebrates encode the core of the RAG recombinase that mediates the V(D)J recombination of the immunoglobulin and T-cell receptor genes. RAG1 and RAG2 homologues (RAG1L and RAG2L) are present in multiple invertebrate phyla, including mollusks, nemerteans, cnidarians, and sea urchins. However, the function of the invertebrates' RAGL proteins is yet unknown. The sea urchins contain multiple RAGL genes that presumably originated in a common ancestral transposon. In this study, we demonstrated that two different RAG1L genes in the sea urchin Paracentrutus lividus (PlRAG1La and PlRAG1Lb) lost their mobility and, along with PlRAG2L, were fully domesticated to carry out different functions. We found that the examined echinoid RAGL homologues have distinct expression profiles in early developmental stages and in adult tissues. Moreover, the predicted structure of the proteins suggests that while PlRAG1La could maintain its endonuclease activity and create a heterotetramer with PlRAG2L, the PlRAG1Lb adopted a different function that does not include an interaction with DNA nor a collaboration with PlRAG2L. By characterizing the different RAG homologues in the echinoid lineage, we hope to increase the knowledge about the evolution of these genes and shed light on their domestication processes.